Personalization, self-advocacy and inclusion: An evaluation of parent-initiated supported living schemes for people with intellectual and developmental disabilities in the Netherlands. (June 2016) - Reindl, Marie-Sol; Waltz, Mitzi; Schippers, Alice
This study focused on parent-initiated supported living schemes in the South of the Netherlands and the ability of these living schemes to enhance participation, choice, autonomy and self-advocacy for people with intellectual or developmental disabilities through personalized planning, support and care. Based on in-depth interviews with tenants, parents and caregivers, findings included that parent-initiated supported housing schemes made steps towards stimulating self-advocacy and autonomy for tenants. However, overprotective and paternalistic attitudes expressed by a significant number of parents, as well as structural constraints affecting the living schemes, created obstacles to tenants' personal development. The study calls for consideration of interdependence as a model for the relationship of parents and adult offspring with disabilities. The benefits and tensions inherent within this relationship must be taken into consideration during inclusive community building.